REGULATORY LEGAL PROTECTION OF OWNERSHIP AND ENTREPRENEURIAL ACTIVITY IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
This article discusses the normative legal protection and specifics of ownership and entrepreneurial activity in Uzbekistan. The socio-economic development strategy implemented in Uzbekistan is attracting domestic and foreign investment by creating a favorable business and investment climate, achieving a strong development of the ownership sector